Exploration and development of domestic thermoelectric cogeneration system - Zheng, Xiaofeng (2013)
Due to quiet operation, no moving parts, long lifespan and compact structure, the thermoelectric application has become a potential green technology which has been used in different areas in the efforts of contributing to achieve simplified and compact system structures and environmental friendliness. Its applications cover a wide range from the earliest application on kerosene lamp to aerospace applications, transportation tools, industrial utilities, medical services, electronic devices and temperature detecting & measuring facilities. Its disadvantage lies in the low conversion efficiency which only converts small amount (for Bi2Te3, up to 5%) of harvested energy to electrical power. It makes the use of the TEG system far from being economically feasible due to long cost recovery period. Consequently, its use is limited to specialised area where it is unnecessary to consider the cost of the thermal energy input and system cost recovery. This research aims to explore a way of widening the application range of thermoelectric generation based on introducing a potential direction of improving energy utilisation efficiency to a higher level by adopting thermoelectric cogeneration concept in residential house. It focuses on investigating the practicality of using thermoelectric applications in domestic sectors where the large amount of heat is exhausted to environment without being used and developing thermoelectric cogeneration system to generate electricity and produce pre-heated water for domestic use by recovering the waste heat from the domestic boiler and utilising the on-site solar energy. With the conversion efficiency given by the current commercially available thermoelectric modules, the optimised heat exchanging regimes and systems for thermoelectric applications have been comprehensively studied from the aspects of system design, integration, experimental study, numerical simulation and modification. The importance and necessity of effective heat exchanging methods have been emphasised by the experimental and numerical proofs for the development of a domestic thermoelectric cogeneration system with higher thermal efficiency. The impacts of this domestic energy solution have been evaluated from the aspects of the improvement for outdoor environment and indoor energy profile, as well as economic benefit.